Dinamikus képességek: Irodalmi feldolgozás - Farkas, Tamás (Vezetéstudomány / Budapest Management Review, 2022)
The literature on dynamic capabilities has undergone a great development over its more than twenty-year history, and has become one of the most researched fields in the management sciences. Despite this development, it is still not considered a unified concept. A number of differences can be identified in the definition of dynamic capabilities, the study subjects, authorial assumptions and the results obtained. The most important findings and the observable contradictions related to dynamic capabilities are presented in this study with the help of a new, modified metamodel. This metamodel includes the theoretical foundations, antecedents, components, context, mediators and impacts on performance dimensions of dynamic capabilities.